1997
DOI: 10.1046/j.1365-2958.1997.4951854.x
|View full text |Cite
|
Sign up to set email alerts
|

IS911‐mediated intramolecular transposition is naturally temperature sensitive

Abstract: SummaryIt is shown here that the bacterial insertion sequence IS911 exhibits a temperature-sensitive transposition phenotype. Previous results have demonstrated that elevated levels of the IS911 transposase OrfAB generate significant quantities of a figure-eight form, created by cleavage and circularization of one of the transposon strands, and of an excised circular form, in which both transposon strands have been circularized. We show here that the level of both types of molecule observed in vivo was greatly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…Even the temperature within a host can change over time if the host is able to elevate its body temperature as an immune response to bacterial infections. Importantly, a number of IS elements exhibit different transposition rates at different temperatures (Cornelis 1980; Haren et al 1997; Kretschmer and Cohen 1979; Ohtsubo et al 2005; Pfeifer and Blaseio 1990). By propagating our experimental populations at a static and stress-free 37°C, many IS elements may have remained relatively quiescent, thus preventing any potential IS expansion.…”
Section: Resultsmentioning
confidence: 99%
“…Even the temperature within a host can change over time if the host is able to elevate its body temperature as an immune response to bacterial infections. Importantly, a number of IS elements exhibit different transposition rates at different temperatures (Cornelis 1980; Haren et al 1997; Kretschmer and Cohen 1979; Ohtsubo et al 2005; Pfeifer and Blaseio 1990). By propagating our experimental populations at a static and stress-free 37°C, many IS elements may have remained relatively quiescent, thus preventing any potential IS expansion.…”
Section: Resultsmentioning
confidence: 99%
“…without frameshifting) from its native promoter within the IS resulted in a high level of deletions and rearrangements in the vector plasmid. In order to facilitate construction of this type of IS 911 derivative, we exploited the observation that OrfAB is inactive at 42°C (Haren et al ., 1997). Bacterial hosts were therefore maintained at 42°C during the appropriate stages of plasmid construction and at all times preceding the mating‐out assays.…”
Section: Resultsmentioning
confidence: 99%
“…The higher transposition activities of these IS elements at 42°C in the ATCC 17616 cells contrasted with the decreased transposition activities of various mobile DNA elements (e.g., Tn3, IS1, IS30, and IS911) in E. coli cells at this temperature (27). The temperature sensitivities of transposition in E. coli have been considered to be the intrinsic properties of the transposases (12). The observation of a simultaneous increase in ATCC 17616 cells of the transposition activities of the seven IS elements belonging to four different IS families (Table 4) suggested that some common host factors affect transposition at high temperatures.…”
Section: Discussionmentioning
confidence: 99%